The Magnolia Story [compact disc, unabridged] - Gaines, Chip, 1974-; Gaines, Joanna, 1978-; Dagostino, Mark (Brilliance Audio, 2016)
The first book from Chip and Joanna Gaines, offering their fans a detailed look at their life together. From the very first renovation project they ever tackled together, to the project that nearly cost them everything. From the childhood memories that shaped them, to the twists and turns that led them to the life they share on the farm today.